2014
DOI: 10.1177/0310057x1404200517
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Airway Equipment: A Survey of Standards across Metropolitan Perth

Abstract: The importance of appropriate equipment to manage the difficult airway has been highlighted by the publication of the Australian and New Zealand College of Anaesthetists (ANZCA) guidelines in 2012. We set out to audit compliance with these guidelines in all public and private sites providing general anaesthesia in metropolitan Perth. Public and private healthcare websites identified 39 sites of which 37 were studied. Institutional and ethics approval was obtained. A tick-box design audit tool, based on the ANZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Our selection of items for inclusion in the questionnaire was based on previous work in which we investigated available DAM resources in the pre-hospital [ 21 ] and ICU [ 22 ] settings in Japan. We also referred to all relevant studies conducted in other countries that similarly assessed EDs [ 28 36 ], ICUs [ 37 41 ], ORs [ 42 45 ], and pre-hospital settings [ 46 48 ]. We then circulated drafts among the survey team members (an epidemiologist, anesthesiologists, and physicians specializing in emergency medicine) and finalized the questionnaire in April 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Our selection of items for inclusion in the questionnaire was based on previous work in which we investigated available DAM resources in the pre-hospital [ 21 ] and ICU [ 22 ] settings in Japan. We also referred to all relevant studies conducted in other countries that similarly assessed EDs [ 28 36 ], ICUs [ 37 41 ], ORs [ 42 45 ], and pre-hospital settings [ 46 48 ]. We then circulated drafts among the survey team members (an epidemiologist, anesthesiologists, and physicians specializing in emergency medicine) and finalized the questionnaire in April 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, to reap the benefits of a well-designed DAT, it is crucial that those who use the DAT are knowledgeable about its organization and have acquired expertise on all included devices through clinical training and simulations. As a dedicated DAT is often present in sites providing general anesthesia, this is not consistently the case according to recent audits and surveys [6, 7]. Importantly, as most airway emergencies develop during the induction phase, incidents can occur throughout the anesthetic process, including extubation [8] and all the way to the postanesthesia care unit.…”
Section: Introductionmentioning
confidence: 99%
“…Previous national and international surveys have produced mixed results but generally show a relatively high availability of DATs in operating departments, ranging between 64% and 92% . An audit study conducted in metropolitan Perth demonstrated that DATs were available at 92% of locations where general anaesthesia was provided, however, no DAT had all equipment recommended by the ANZCA . Unfortunately, we discovered relatively low availability of DATs in remote anaesthetizing locations, where access to a well‐equipped DAT may be even more important.…”
Section: Discussionmentioning
confidence: 99%